Robust control of wind turbine based on doubly-fed induction generator optimized by genetic algorithm - Noureddine Elmouhi; Ahmed Essadki; Hind Elaimani (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
In this research paper we will cover the study of the modelling and the control methods of the variable speed wind turbine based on doubly-fed induction generator (DFIG). It represents the most stressed structure given its distinctive characteristics. To control the electrical powers generated by this system independently, the vector control with the stator flux orientation is founded according to two techniques: i) the control of the powers by the backstepping technique and ii) the robust control based on the active disturbances rejection control. After the synthesis of the controllers of those two methods, their performances will be tested and compared to evaluate their effectiveness. We are mainly interested in the robustness test of the two control strategies with respect to the internal parameters’ fluctuation of the generator. The computing of the different parameters regulators of these two strategies is carried out using a genetic algorithm. This computing method makes it possible to arrive at an optimal solution of the DFIG power control. The different parts are simulated using MATLAB/Simulink environment.